Pneumonia complicated by SARS-coV-2 infection in three patients with ankylosing spondylitis who are on anti-TNF therapy: Case-based review - Serdar Kaymaz; Ugur Karasu; Veli Çobankara; Hakan Alkan; Firdevs Ulutas (Indian Journal of Rheumatology)
The mortality rate for the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic is increasing worldwide with each passing day. The risk factors for mortality include advanced age and comorbidities. It is still uncertain whether biological agents pose a risk for the progression of SARS-CoV-2. Although there are studies suggesting the use of biological agents in the literature, there are also studies suggesting the discontinuation of biological agents during SARS-CoV-2. In this study, we aimed to determine whether anti-tumor necrosis factor (anti-TNF-α agents) therapy, which is one of the biological agents commonly used in rheumatology clinics, has an effect on the clinical course of SARS-CoV-2 infection, and to review the literature. We searched the MEDLINE/PubMed and SCOPUS databases until the date of August 15, 2020, using the following keywords: SARS-CoV-2 and anti-TNF-α agents. We reviewed abstracts and retrieved the relevant articles. We reported the clinical manifestation and disease course of SARS-CoV-2 pneumonia in three patients with ankylosing spondylitis who were receiving anti-TNF-α agents. All patients in our case series had a mild course similar to the most cases reported in the literature.